Polishing composition suitable for barrier layer of copper interconnection structure of integrated circuit and application of polishing composition
By using covalent grafting technology of silane-capped polymer and silica sol particles in the polishing composition, the problem of defects in the polishing process of the copper interconnect structure barrier layer in the CMP process is solved, and lower surface defects and higher electrical properties are achieved.
Patent Information
- Application Number
- CN202411746806.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The existing chemical mechanical polishing (CMP) process has defects in the polishing process of the barrier layer of copper interconnect structure, such as residual polishing liquid particles and scratches, resulting in damage to the interconnection's electrical performance. The existing improvement measures have problems such as foaming properties and adsorption residues.
Using a polishing composition including an oxidant, silica sol particles, silane capping polymer, complexing agent, pH adjusting agent and corrosion inhibitor, the aggregation and hardness of the silica sol particles are improved and the surface defects after polishing are reduced.
It effectively reduces surface defects after polishing, improves the electrical performance of copper interconnect structures, and meets the high requirements of advanced processes for defect control.
Smart Images

Figure BDA0005163942020000071 
Figure BDA0005163942020000072 
Figure BDA0005163942020000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical mechanical polishing, and in particular to a chemical mechanical polishing composition suitable for a barrier layer of a copper interconnection structure of an integrated circuit and an application thereof. Background Art
[0002] The demand for smaller chip size and higher computing / storage capacity can be achieved by reducing line width and increasing the number of stacking layers, which requires good flatness between chip layers. Currently, the only technology to achieve good inter-layer flatness in chip manufacturing is chemical mechanical polishing (CMP).
[0003] Copper has been widely used as a wiring metal in integrated circuit manufacturing instead of aluminum, mainly due to the advantages of Cu wiring, such as lower resistivity and RC delay, better resistance to electromigration, etc. The dual Damascene process is used to make the copper wiring layer. The general steps are as follows: first, a groove is etched on the dielectric layer; then a copper barrier layer such as Ta / TaN is filled in the groove. In order to improve the adhesion between copper and the groove, a copper seed layer is deposited; finally, the electroplating method is used to fill the groove with copper; finally, the copper wiring layer is CMPed.
[0004] The copper wiring layer CMP process is mainly divided into three steps. The first step is to use copper polishing liquid to quickly remove a large amount of copper under high polishing pressure; the second step is to use copper polishing liquid to remove the remaining copper and stop at the barrier layer under low polishing pressure; the third step is to use barrier layer polishing liquid to remove barrier layer metal, dielectric layer and a small amount of copper layer. Defect control in the third step of polishing is the key. The types of defects include polishing liquid particle residue, polishing byproduct residue, scratches, metal corrosion, water marks, etc. Among them, particle residue and scratches have a greater impact on the signal transmission of interconnect lines. As the chip process is reduced, the width of the interconnect line is getting lower and lower, and the requirements for defect control are getting higher and higher. Scratches will reduce the thickness of the interconnect metal and increase the resistance value. CMP defects will also accelerate the aging and failure of the chip, which will lead to product failure and cause greater losses. As the chip process is reduced, the damage of defects to the electrical performance of the interconnect line is amplified. Therefore, reducing post-CMP defects is a long-term goal of polishing liquid formulation development.
[0005] Patent CN 102161879 B adds polyoxyethylene phenyl ether sulfate to the polishing liquid, which is adsorbed on the surface of the polished material to reduce polishing defects. However, this type of substance has strong foaming properties, which is not conducive to production, and its adsorption on the polished material will cause organic residues. Patent TW 200938614A adds imine compounds and carbonates to the polishing liquid containing polyvinylpyrrolidone, which improves the pH buffering effect of the slurry, reduces pH value fluctuations, and reduces the defects of TEOS and copper polishing surfaces. However, polyvinylpyrrolidone will increase the potential of polishing particles, which is not conducive to the stability of polishing particles. Patent CN111004579A discloses a special chelating agent and surfactant combination composition to reduce defects. Patent CN 109690741 A improves the defects of the polished surface by controlling the potential of the polishing particles and the polished surface. As the chip feature size decreases, the control requirements for defects are higher, and it is necessary to improve the formulation components of the polishing liquid to meet the requirements of advanced processes. Summary of the invention
[0006] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a polishing composition suitable for chemical mechanical polishing of a copper interconnect structure barrier layer in integrated circuit manufacturing, wherein the polishing composition can improve the polished surface defects of the copper interconnect structure barrier layer.
[0007] Another object of the present invention is to provide the use of the polishing composition suitable for chemical mechanical polishing of the barrier layer of the copper interconnect structure in the manufacture of integrated circuits in chemical mechanical polishing.
[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0009] A polishing composition suitable for chemical mechanical polishing of a copper interconnection structure barrier layer in integrated circuit manufacturing, comprising an oxidant, silica sol particles, a silane-terminated polymer, a complexing agent, a pH regulator, and a corrosion inhibitor.
[0010] In a preferred embodiment, the polishing composition includes the following components in percentage by weight: 0.01wt%-5wt% of an oxidizing agent, 0.1wt%-30wt% of silica sol particles, 0.005wt%-0.5wt% of a silane-terminated polymer, 0.005wt%-1wt% of a complexing agent, 0.01wt%-1wt% of a pH regulator, 0.001wt%-1wt% of a corrosion inhibitor, and the balance is deionized water.
[0011] In a specific embodiment, the silica sol particles are silica sol prepared by any one of a single silicon method, an ion exchange method, and a sol-gel method, preferably a silica sol prepared by an ion exchange method or a sol-gel method.
[0012] In a preferred embodiment, the size of the abrasive particles is 10-300 nm, preferably 50-150 nm.
[0013] In a specific embodiment, the silane on the silane-terminated polymer is preferably any one of 3-aminopropyltriethoxysilane, triethoxysilane (polyethylene glycol bistriethoxysilane, Kanto Chemical), N-aminoethyl-3-aminopropylmethyldimethoxysilane, aminopropylmethyldiethoxysilane, and 3-aminopropyltrimethoxysilane.
[0014] In a specific embodiment, the silanes at both ends of the polymer molecular chain can be one type or two different types.
[0015] In a specific embodiment, the type of polymer on the silane-terminated polymer can be any one of polyether polyol, polyethylene glycol, and polyvinyl alcohol. The molecular weight of the polymer is 200-100000 g / mol.
[0016] In a specific embodiment, the polymer is a polyether polyol, and the HLB value of the polyether polyol is greater than 10.
[0017] In a specific embodiment, the complexing agent is selected from one or more of glycine, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, sodium ethylenediaminetetramethylene phosphate, oxalic acid, acetic acid, citric acid, malonic acid, nitrile triacetic acid, ethylenediaminetetramethylenephosphonic acid, and aminotrimethylenephosphonic acid, preferably any one of glycine, oxalic acid, citric acid or ethylenediaminetetraacetic acid, more preferably glycine or citric acid.
[0018] In a specific embodiment, the pH regulator is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, ethanolamine, diethanolamine, triethanolamine, piperazine, aniline, azole compounds, potassium hydroxide, sodium hydroxide, guanidine compounds, and alkali metal alkoxides, preferably any one of tetraethylammonium hydroxide, ethanolamine, triazole, potassium hydroxide, and guanidine carbonate, and more preferably tetraethylammonium hydroxide or guanidine carbonate.
[0019] In a specific embodiment, the pH value of the polishing composition is 8-12, preferably 9-11.
[0020] In a specific embodiment, the corrosion inhibitor is selected from at least any one of aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3,5-diamino-1,2,4-triazole, benzotriazole, cytosine, uracil, and 2-methyl-4-isothiazolinetrione, preferably any one of aspartic acid, 1,2,4-triazole, 2-methyl-4-isothiazolinetrione, tetrazole or 3,5-diamino-1,2,4-triazole.
[0021] In a specific embodiment, the oxidizing agent is hydrogen peroxide.
[0022] In another aspect, the polishing composition is used in chemical mechanical polishing of a copper interconnection barrier layer in integrated circuit manufacturing.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The silane-terminated polymer component contained in the polishing composition of the present invention, after the siloxane group at the end of the molecular chain is hydrolyzed, condenses with the silanol group on the silica sol particles to form a covalent bond, and the polymer chain segment is grafted onto the silica sol particles in the form of a covalent bond. After the silane-terminated polymer of the present invention is grafted onto the silica sol particles, the agglomeration of the silica sol particles can be improved, the hardness of the silica sol particles can be reduced, and the surface defects of the material after polishing can be reduced. DETAILED DESCRIPTION
[0025] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.
[0026] A polishing composition suitable for chemical mechanical polishing of a barrier layer of a copper interconnect structure in integrated circuit manufacturing, the chemical mechanical polishing composition comprising an oxidant, silica sol, a silane-terminated polymer, a complexing agent, a pH regulator, a corrosion inhibitor and deionized water. Specifically, the mass percentage of each component of the chemical mechanical polishing composition is: 0.01wt%-5wt% of the oxidant, 0.1wt%-30wt% of silica sol particles, 0.005wt%-0.5wt% of the silane-terminated polymer, 0.005wt%-1wt% of the complexing agent, 0.01wt%-1wt% of the pH regulator, 0.001wt%-1wt% of the corrosion inhibitor, and the balance is deionized water.
[0027] Wherein, the preparation method of the silica sol abrasive particles is not particularly limited, for example, any one of the elemental silicon method, ion exchange method, and sol-gel method. Without any restrictions, the specific preparation method can refer to the prior art, or the corresponding abrasive can be directly purchased on the market. In addition, the size of the abrasive particles is 10-300nm, including but not limited to 20nm, 50nm, 75nm, 100nm, 120nm, 150nm, 180nm, 200nm, 230nm, 250nm, 270nm, 285nm, 300nm, preferably 50-150nm. The amount of silica sol added is 0.01wt%-30wt%, for example, including but not limited to 0.01wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, etc.
[0028] As the silane-terminated polymer, the end-capped silane is preferably 3-aminopropyltriethoxysilane, triethoxysilane (polyethylene glycol bistriethoxysilane, Kanto Chemical), N-aminoethyl-3-aminopropylmethyldimethoxysilane, aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane. The silanes at both ends of the polymer molecular chain can be one or two different silanes.
[0029] As the silane-terminated polymer, the type of polymer can be polyether polyol, polyethylene glycol, polyvinyl alcohol; the molecular weight of the polymer is 200-100000 g / mol, for example, including but not limited to 200, 500, 800, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 20000, 30000, 40000, 50000, 60000, 70000, 80000, 90000, 100000 g / mol, etc., preferably 200-20000 g / mol molecular weight. The amount of the polymer added is 0.005wt%-0.5wt%, for example, including but not limited to 0.005wt%, 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%. Too much polymer addition will result in organic matter remaining on the surface after polishing, and too little addition will not have any effect. Wherein, the HLB value of the polyether polyol is ≥10. For example, including but not limited to 10, 11, 12, 13, 15, 20, etc.
[0030] The complexing agent is selected from one or more of glycine, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, sodium ethylenediaminetetramethylene phosphate, oxalic acid, acetic acid, citric acid, malonic acid, nitrile triacetic acid, ethylenediaminetetramethylenephosphonic acid, and aminotrimethylenephosphonic acid, preferably any one of oxalic acid, citric acid or ethylenediaminetetraacetic acid, more preferably glycine and citric acid.
[0031] The amount of the complexing agent added is 0.005wt%-1wt% of the mass of the polishing composition, for example, including but not limited to 0.005wt%, 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%. The addition of the complexing agent in the polishing composition is conducive to complexing free metal ions in the polishing liquid and promoting the removal of copper. Too much addition will increase the roughness of the polishing surface, and too little addition will not achieve the required copper removal rate, and copper compound residues are likely to be generated on the surface of the polishing pad after polishing.
[0032] The pH regulator is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, ethanolamine, diethanolamine, triethanolamine, piperazine, aniline, azole compounds, potassium hydroxide, sodium hydroxide, guanidine compounds, and alkali metal alkoxides, preferably any one of tetraethylammonium hydroxide, ethanolamine, triazole, potassium hydroxide, and guanidine carbonate, and more preferably tetraethylammonium hydroxide, guanidine carbonate, or potassium hydroxide.
[0033] The pH adjuster is added in an amount of 0.01wt%-1wt% of the mass of the polishing composition. Specifically, the pH value of the polishing composition is adjusted to 8-12 by the pH adjuster, for example, including but not limited to 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12. Preferably, the pH value of the polishing composition is adjusted to 9-11. The polishing composition within this pH range is more suitable for a barrier layer polishing process.
[0034] The corrosion inhibitor is selected from aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3,5-diamino-1,2,4-triazole, benzotriazole, cytosine, uracil, 2-methyl-4-isothiazoline trione, preferably any one of aspartic acid, 1,2,4-triazole, 2-methyl-4-isothiazoline trione, tetrazole or 3,5-diamino-1,2,4-triazole. The amount of the corrosion inhibitor added is 0.001wt%-1wt% of the mass of the polishing composition, for example, including but not limited to 0.001wt%, 0.01wt%, 0.02wt%, 0.06wt%, 0.08wt%, 0.1wt%, 0.2wt%, 0.4wt%, 0.5wt%, 1wt%. The addition of corrosion inhibitors to the polishing composition can form a protective film with the copper surface, inhibit static corrosion of copper, and regulate the removal rate of copper.
[0035] The pH adjuster is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, ethanolamine, diethanolamine, triethanolamine, aniline, potassium hydroxide, sodium hydroxide, guanidine compounds, and alkali metal alkoxides, preferably any one of tetramethylammonium hydroxide, ethanolamine, potassium hydroxide, and guanidine carbonate, and more preferably tetramethylammonium hydroxide, ethanolamine, or potassium hydroxide.
[0036] The pH adjuster is added in an amount of 0.01wt%-1wt% of the mass of the polishing composition. Specifically, the pH value of the polishing composition is adjusted to 8-12 by the pH adjuster, for example, including but not limited to 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0. Preferably, the pH value of the polishing composition is adjusted to 9-11. The polishing composition within this pH range is more suitable for copper polishing process.
[0037] The oxidant is hydrogen peroxide. Hydrogen peroxide first oxidizes copper into CuO / Cu2O to form a softened copper oxide film, which is removed by mechanical action and the complexing action of the complexing agent. The amount of the oxidant added is 0.01wt%-5wt% of the mass of the polishing composition, for example, including but not limited to 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%. If too little hydrogen peroxide is added, not only the required copper removal rate cannot be achieved, but also the copper surface roughness after polishing is high, and too much addition will inhibit the copper removal rate.
[0038] The polishing composition of the present invention has the advantage that the silane-terminated polymer component contained in the polishing composition of the present invention, after the siloxane group at the end of the molecular chain is hydrolyzed, condenses with the silanol group on the silica sol particles to form a covalent bond, and the polymer chain segment is grafted onto the silica sol particles in the form of a covalent bond. After the silane-terminated polymer of the present invention is grafted onto the silica sol particles, the agglomeration of the silica sol particles can be improved, the hardness of the silica sol particles can be reduced, and the surface defects of the material after polishing can be reduced.
[0039] The present invention is further explained below by more specific examples, but does not constitute any limitation.
[0040] Other materials, instruments and reagents in the examples and comparative examples of the present invention are all purchased from commercial sources. The silane-terminated polymers described in the examples of the present invention can be purchased from Guangzhou Carbon Water Technology or Wacker Chemie.
[0041] Polishing liquid preparation
[0042]
[0043]
[0044] The substances in the table were mixed evenly, the balance in the formula was supplemented with deionized water, and the pH was adjusted to 10.0 with potassium hydroxide. The amount of potassium hydroxide used is described in the following Table 1.
[0045] Table 1 Chemical mechanical polishing liquid composition table of comparative examples and embodiments
[0046]
[0047]
[0048] After the above substances are mixed uniformly, 0.8 wt % of hydrogen peroxide is added thereto and mixed uniformly to obtain a sample for polishing.
[0049] In order to reduce the experimental error caused by the decomposition of hydrogen peroxide over time, the samples were used within 3 hours after preparation.
[0050] Polishing rate evaluation
[0051] In the following embodiments, the instruments and parameters used in the polishing of copper, barrier layer dielectric Ta and dielectric layer TEOS are as follows:
[0052]
[0053] In the following embodiments, the copper wafer used for polishing is a 1000A copper film electroplated on a 600 micron (100) crystal plane single crystal silicon substrate, and the copper wafer size is 12 inches. The TEOS wafer used for polishing is a 2000A TEOS film deposited on a 600 micron (100) crystal plane single crystal silicon substrate.
[0054] On the diameter of a 12-inch wafer, take the zero point as the starting point, select a point every 1 cm in the positive and negative directions, and take a total of 28 points. Use a four-probe conductivity meter to test the conductivity of the points in the selected area on the copper wafer, so as to calculate the thickness of the copper wafer. The difference in thickness of the copper wafer before and after polishing divided by the polishing time is the polishing rate.
[0055] Surface defect detection
[0056] Use a surface defect detector to measure the number of surface defects.
[0057] Example
[0058] The types and contents of the substances added to the polishing liquid formulas used in the examples and comparative examples are shown in Table 1, and the balance is deionized water. The content of the oxidant added to the polishing liquid formulas of the examples and comparative examples is 0.8 wt %.
[0059] The polishing liquid prepared in the embodiment and comparative example is used for chemical mechanical polishing of the barrier layer of the copper interconnect structure in integrated circuit manufacturing according to the above method to evaluate the polishing rate and surface defects. The relevant evaluation results are shown in Table 2.
[0060] Table 2 Polishing rate and defect repair amount of comparative examples and examples
[0061]
[0062] As can be seen from the above table, compared with Example 1, the defect repair value of Example 1 with the addition of triethoxysilane-terminated polyethylene glycol has been significantly improved. Compared with Example 1, the defect repair values of Comparative Examples 2-3 with the addition of polyethylene glycol or triethoxysilane are all lower than those of Example 1 with the addition of triethoxysilane-terminated polyethylene glycol. The above shows that silane-terminated polymers can effectively repair defects.
[0063] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A polishing composition suitable for a barrier layer of an integrated circuit copper interconnect structure, characterized in that: The invention comprises an oxidant, silica sol particles, a silane-terminated polymer, a complexing agent, a pH regulator and a corrosion inhibitor.
2. The polishing composition according to claim 1, wherein The polishing composition comprises the following components in percentage by weight: 0.01wt%-5wt% of an oxidizing agent, 0.1wt%-30wt% of silica sol particles, 0.005wt%-0.5wt% of a silane-terminated polymer, 0.005wt%-1wt% of a complexing agent, 0.01wt%-1wt% of a pH regulator, 0.001wt%-1wt% of a corrosion inhibitor, and the balance is deionized water.
3. The polishing composition according to claim 1 or 2, characterized in that The silica sol particles are silica sols prepared by any one of a single silicon method, an ion exchange method, and a sol-gel method, and are preferably silica sols prepared by an ion exchange method or a sol-gel method.
4. The polishing composition according to claim 1 or 2, characterized in that The silane in the silane-terminated polymer is selected from any one of 3-aminopropyltriethoxysilane (APTES), triethoxysilane (TES), N-aminoethyl-3-aminopropylmethyldimethoxysilane, aminopropylmethyldiethoxysilane, and 3-aminopropyltrimethoxysilane; Preferably, the silanes at both ends of the silane-terminated polymer molecular chain are selected from the same one or two different ones.
5. The polishing composition according to claim 4, characterized in that The type of polymer in the silane-terminated polymer is selected from any one of polyether polyol, polyethylene glycol, and polyvinyl alcohol; preferably, the molecular weight of the polymer is 200-100000 g / mol; and / or The polymer is a polyether polyol, and preferably the HLB value of the polyether polyol is greater than 10.
6. The polishing composition according to claim 1 or 2, characterized in that The complexing agent is selected from one or more of glycine, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, sodium ethylenediaminetetramethylene phosphate, oxalic acid, acetic acid, citric acid, malonic acid, nitrile triacetic acid, ethylenediaminetetramethylenephosphonic acid, and aminotrimethylenephosphonic acid, preferably any one of glycine, oxalic acid, citric acid or ethylenediaminetetraacetic acid, more preferably glycine or citric acid.
7. The polishing composition according to claim 1 or 2, characterized in that The pH regulator is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, ethanolamine, diethanolamine, triethanolamine, piperazine, aniline, azole compounds, potassium hydroxide, sodium hydroxide, guanidine compounds, and alkali metal alkoxides, preferably any one of tetraethylammonium hydroxide, ethanolamine, triazole, potassium hydroxide, and guanidine carbonate, and more preferably tetraethylammonium hydroxide or guanidine carbonate; Preferably, the pH value of the polishing composition is 8-12, preferably 9-11.
8. The polishing composition according to claim 1 or 2, wherein The corrosion inhibitor is selected from at least any one of aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3,5-diamino-1,2,4-triazole, benzotriazole, cytosine, uracil, and 2-methyl-4-isothiazolinetrione, preferably any one of aspartic acid, 1,2,4-triazole, 2-methyl-4-isothiazolinetrione, tetrazole or 3,5-diamino-1,2,4-triazole.
9. The polishing composition according to claim 1 or 2, characterized in that The oxidant is hydrogen peroxide.
10. Use of the polishing composition for a barrier layer of a copper interconnect structure of an integrated circuit as claimed in any one of claims 1 to 9 in chemical mechanical polishing of the barrier layer of a copper interconnect structure in integrated circuit manufacturing.
Citation Information
Patent Citations
Polishing composition and polishing method using the same
CN102161879B
CMP polishing solution and polishing method
CN109690741A
Alkaline polishing solution for reducing CMP defects of multi-layer copper interconnection barrier layer and preparation method of alkaline polishing solution
CN111004579A
CMP slurry composition and process for planarizing copper containing surfaces provided with a diffusion barrier layer
TW200938614A